Tortricidae from Venezuela (Lepidoptera: Tortricidae) - J. Wojtusiak (SHILAP Revista de lepidopterología, 2006)
The species described to this date from Venezuela are listed. 34 new species and 9 new genera are described:Cochylini: Henricus glaesarius Razowski & Wojtusiak, sp. n., H. montanus Razowski & Wojtusiak, sp. n., Phalonidiacholovalva Razowski & Wojtusiak, sp. n., P. claudia Razowski & Wojtusiak, sp. n., Cochylis cataphracta Razowski& Wojtusiak, sp. n.; Euliini: Imelcana Razowski & Wojtusiak, gen. n., I. camelina Razowski & Wojtusiaksp. n., Meridulia Razowski & Wojtusiak, gen. n., M. meridana Razowski & Wojtusiak, sp. n., M. zerpana Razowski& Wojtusiak, sp. n., M. chaenostium Razowski & Wojtusiak, sp. n., Paramulia Razowski & Wojtusiak, gen. n., P.laculetana Razowski & Wojtusiak, sp. n., Oregocerata colossa Razowski & Wojtusiak, sp. n., Ditrifa Razowski &Wojtusiak, gen. n., D. trifida Razowski & Wojtusiak, sp. n., Transtillaspis armifera Razowski & Wojtusiak, sp. n.,Netechma gnathocera Razowski & Wojtusiak, sp. n., Seticosta niveonigra Razowski & Wojtusiak, sp. n., Bonagotapiosana Razowski & Wojtusiak, sp. n., Meridagena Razowski & Wojtusiak, gen. n., M. bicerithium Razowski &Wojtusiak, sp. n., Orthocomotis chlamyda Razowski & Wojtusiak, sp. n.; Atteriini: Sisurcana batalloana Razowski& Wojtusiak, sp. n.; Archipini: Argyrotaenia cordillerae Razowski & Wojtusiak,sp. n., A. ferruginea Razowski &Wojtusiak, sp. n., Clepsis nevadae Razowski & Wojtusiak, sp. n.; Chlidanotinae: Heppnerographa circinnata Razowski& Wojtusiak, sp. n.; Eucosmini: Epinotia chlorizans Razowski & Becker, sp. n., Zerpanotia Razowski &Wojtusiak, gen. n., Z. zerpana Razowski & Wojtusiak, sp. n., Quebradnotia Razowski & Wojtusiak, gen. n., Q.ouralia Razowski & Wojtusiak, sp. n., Q. quebradae Razowski & Wojtusiak, sp. n., Q. chasigrapha Razowski &Wojtusiak, sp. n., Laculataria Razowski & Wojtusiak, gen. n., L. asymmetra Razowski & Wojtusiak, sp. n., L.chlorochara Razowski & Wojtusiak, sp. n., L. chondrites Razowski & Wojtusiak, sp. n., Crocidosema venata Razowski& Wojtusiak, sp. n., Mesochariodes Razowski & Wojtusiak, gen. n., M. polytrichota Razowski & Wojtusiak,sp. n., and M. secunda Razowski & Wojtusiak, sp. n. Two species are new to Venezuela: Quebradnotia nolckeniana(Zeller, 1877) and Cydia guttifera (Meyrick, 1913).